2011
DOI: 10.1103/physrevb.84.075479
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative modeling ofin situx-ray reflectivity during organic molecule thin film growth

Abstract: Synchrotron-based x-ray reflectivity is increasingly employed as an in situ probe of surface morphology during thin film growth, but complete interpretation of the results requires modeling the growth process. Many models have been developed and employed for this purpose, yet no detailed, comparative studies of their scope and accuracy exists in the literature. Using experimental data obtained from hyperthermal deposition of pentane and diindenoperylene (DIP) on SiO2, we compare and contrast three such models,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 56 publications
3
77
1
Order By: Relevance
“…Elongated islands resemble the shape of islands in PFP films, 20,29 but there are also more compact islands as in PEN thin films. 16,30 On top of some islands, molecular step edges with a height of ∼15 Å can be discerned, which points to upright standing PEN and PFP molecules.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Elongated islands resemble the shape of islands in PFP films, 20,29 but there are also more compact islands as in PEN thin films. 16,30 On top of some islands, molecular step edges with a height of ∼15 Å can be discerned, which points to upright standing PEN and PFP molecules.…”
Section: Resultsmentioning
confidence: 97%
“…PFP only grows in a layer by layer fashion for 1 -2 MLs 20 and PEN for less than 4 MLs on top of silica. 30 Beyond this thickness, surface roughening leads to holes in PEN layers that get filled with PFP and vice versa, reducing the structural definition of the superlattice. Using molecules that exhibit a more pronounced layer-by-layer growth such as DIP, PTCDI-C8 or C60 would enable an extended superlattice with more periods.…”
Section: Resultsmentioning
confidence: 99%
“…12,17,20,26 We found that the pentacene grown on the polymer brush layers underwent significant incomplete condensation, where desorption of pentacene molecules from the substrate surface becomes important. The incomplete condensation was more severe at higher substrate temperatures (T ∼ T g,surf ) than at lower substrate temperatures (T < T g,surf ).…”
Section: Introductionmentioning
confidence: 90%
“…X-ray scattering measurements enable real-time structural monitoring during the earlystage growth of a small molecule organic layer. X-ray scattering in the anti-Bragg configuration 12,[16][17][18][19][20][21][22] or energydispersive x-ray reflectivity [23][24][25] methods are useful tools for characterizing the coverage of individual small molecule organic thin film layers in real-time. Real-time x-ray scattering methods have been applied to organic films deposited onto bare SiO 2 or SAM-treated SiO 2 surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In situ X-ray scattering techniques fulfill these conditions. For epitaxial systems, measurements at fixed points of a crystal truncation rod have been successfully performed by Braun et al (2003), Krause et al (2004), Jenichen et al (2007), Woll et al (2011) and Chinta & Headrick (2014). However, this method is not applicable for polycrystalline coatings.…”
Section: Introductionmentioning
confidence: 99%